2015
DOI: 10.1097/fjc.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peripheral Vascular Resistance for the Association Between Major Depression and Cardiovascular Disease

Abstract: Abstract:Major depression and cardiovascular diseases are 2 of the most prevalent health problems in Western society, and an association between them is generally accepted. Although the specific mechanism behind this comorbidity remains to be elucidated, it is clear that it has a complex multifactorial character including a number of neuronal, humoral, immune, and circulatory pathways. Depression-associated cardiovascular abnormalities associate with cardiac dysfunctions and with changes in peripheral resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 132 publications
(235 reference statements)
0
9
0
Order By: Relevance
“…We suggest that CMS-induced endothelial dysfunction contributes to changes in blood perfusion of vital organs which, in turn, can contribute to the pathology and comorbidity between major depression and cardiovascular diseases. In accordance with the hypothesis of an association between depression symptoms and small artery function (9), escitalopram treatment partially normalized the balance between the different pathways of endotheliumdependent relaxation. Changes in EDH-like and COX-2-dependent relaxation correlated with the responsiveness of rats to escitalopram treatment.…”
Section: Perspectives and Significancementioning
confidence: 50%
See 1 more Smart Citation
“…We suggest that CMS-induced endothelial dysfunction contributes to changes in blood perfusion of vital organs which, in turn, can contribute to the pathology and comorbidity between major depression and cardiovascular diseases. In accordance with the hypothesis of an association between depression symptoms and small artery function (9), escitalopram treatment partially normalized the balance between the different pathways of endotheliumdependent relaxation. Changes in EDH-like and COX-2-dependent relaxation correlated with the responsiveness of rats to escitalopram treatment.…”
Section: Perspectives and Significancementioning
confidence: 50%
“…Furthermore, we have shown that the CMS susceptibility is also associated with reduced endothelium-dependent relaxation due to suppressed EDH-like pathway despite upregulation of the NO and cyclooxygenase 2 (COX-2)-dependent pathways in rat mesenteric resistance arteries (8). Importantly, these arteries are essential for the control of the blood pressure and tissue perfusion, but knowledge about their abnormalities in association with depression symptoms is limited (9). Since increased oxidative stress is common for both the endothelial dysfunction (67) and major depression disorder (46), we hypothesized that it might be one of the links between depression and cardiovascular diseases.…”
mentioning
confidence: 99%
“…Depression and vascular disease are both common among the elderly, and cardiac dysfunction in association with depression is well documented [46, 61, 62]. These observations may provide clues about the mechanistic relationships, as depression-associated changes of peripheral vascular resistance are essential for the association of MDD with cardiovascular disease [63, 64]. …”
Section: Resultsmentioning
confidence: 99%
“…Hypertension has been identified as one of the established risk factors in PAD 15 and has also been identified as a potential mechanism for the association between depression and cardiovascular disease, including the coronary arteries, but potentially also for the peripheral arteries. 16 Stress and depression may trigger a cascade of hemodynamic changes, including higher sympathetic tone, increasing levels of noradrenaline, and increased vasoconstriction, as well as elevation in systemic arterial pressure. 16 Although hypertension is a modifiable risk factor, the treatment of hypertension in PAD is not as prominently targeted as one of the metrics that define high-quality PAD management, although one can argue that hypertension as a diagnosis warrants treatment in itself to manage cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…16 Stress and depression may trigger a cascade of hemodynamic changes, including higher sympathetic tone, increasing levels of noradrenaline, and increased vasoconstriction, as well as elevation in systemic arterial pressure. 16 Although hypertension is a modifiable risk factor, the treatment of hypertension in PAD is not as prominently targeted as one of the metrics that define high-quality PAD management, although one can argue that hypertension as a diagnosis warrants treatment in itself to manage cardiovascular risk. 17…”
Section: Discussionmentioning
confidence: 99%